Optically manipulated control over micron-scale signalling dynamics for directing cellular differentiation and migration - Ware, James (2017)
Cellular microenvironments are an important area of study, and their implications with regard to development, tissue function, and disease, mean that they have particular relevance in tissue engineering. The development of tissue engineered therapeutics is underpinned by the understanding of how the cells exist in their natural environment. A fundamental lack of insight into the signalling mechanisms within microenvironments, due to in part a lack of appropriate technologies, has meant that the therapeutic potential of tissue engineering is limited. To this end, the development of a micropatterning technology that enables control over solute signalling dynamics on the micron scale has been investigated. A bespoke holographic optical tweezers (HOTs) system was used to precisely position cells and controlled release vehicles into three-dimensional arrangements that resemble basic cellular micro-architectures. Via optical manipulation, release vehicles could be patterned to create solute release patterns to mimic signalling events in vitro. A proof of concept was established to demonstrate fluorophore release from microparticles positioned with high precision, into previously unobtainable micron-scale patterns. Such developments required optimisation of the system and protocols, for use with cell and microparticle manipulation and, creating a tool-set suitable for address unsolved biological questions. Biological investigations were completed to demonstrate how the HOTs can be used to control zonal cell differentiation and migration. These processes are paramount to cell microenvironment function, and this study has shown that the HOTs patterning setup is capable of achieving such signalling models in vitro. Herein is presented compelling evidence that optically manipulated release sources can achieve new levels of precision over signalling dynamics, over the length scales suitable for even the smallest cell microenvironments. It is hoped that through the better in vitro modelling of such cellular microenvironments and other signalling events, investigators will be able to elucidate new mechanisms through which cells proliferate and function.